ANALYSIS OF USER ACCEPTANCE OF THE MULTIPURPOSE FINANCING ANALYSIS APPLICATION AT BANK SYARIAH X WITH THE UTAUT MODEL - Rizka Tri Cahyaning Ati; Diah Krisnaningsih (International Journal of Economic Integration and Regional Competitiveness, 2025)
Objective: This research aims to determine the level of user acceptance of the Excel application for multi-purpose financing analysis at Bank Syariah X. The use of the application in the financing business process is expected to facilitate the work of AO financing analysts, supported by good technological facilities. Method: The method used by the author is qualitative, delving into the acceptance of computer technology at Bank Syariah X as a tool for analyzing multipurpose financing, and conducting interviews and direct observations to achieve optimal results. Results: The results obtained from this study indicate that the level of acceptance among employees of Bank Syariah X towards the Excel application for multi-purpose financing analysis is considered quite good, with 75% of respondents stating that the use of the application is easy. However, other sources also believe that the use of this Excel application is quite complicated and still requires better improvements. Novelty: This study provides insights into employee acceptance of technology in Islamic banking, specifically examining the implementation of an Excel-based analysis tool in financing activities—a topic that has rarely been explored in previous research.